Sosialisasi dan Pelatihan Pemanfaatan Limbah Kulit Kopi sebagai Sumber Energi Alternatif bagi Gabungan Kelompok Tani di Kecamatan Silo, Kabupaten Jember: Socialization and Training on Utilizing Coffee Husk Waste as an Alternative Energy Source for Farmer Groups in Silo Subdistrict, Jember District - Nashrullah, Muhammad Dimyati; Sanata, Andi; Sholahuddin, Imam; Sugara, Imam Rudi; Prasetyo, Dani Hari Tunggal (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The Silo subdistrict is one of the coffee-producing villages, with a production amounting to more than 40% of the total coffee production in Jember Regency. The coffee processing produces coffee husk waste, which is often discarded into the environment and potentially causes pollution. Coffee husk waste has a high calorific value and is suitable for use as biomass fuel to produce syngas through gasification methods. The partner for this community service is GAPOKTAN Suka Maju, located in Pace Village, Silo Subdistrict, Jember Regency. GAPOKTAN Suka Maju is led by Mr. Zainal Arifin, who has 30 members. This community service aims to provide knowledge to GAPOKTAN Suka Maju members about the environmental impact of coffee husk waste disposal and the utilization of coffee husk waste as an energy source through gasification methods. The community service method consists of pre-activities, activity implementation, and evaluation. The pre-activities include designing the gasification equipment, making the gasification equipment, and drying the coffee husk waste. The implementation consists of socializing the environmental impact of coffee husk waste disposal, the energy potential of coffee husk waste, and training in gasification equipment. The results show a significant increase in the participants' understanding of the environmental impact of coffee husk waste disposal, the energy potential of coffee husk waste, and the gasification method and equipment to convert coffee husk waste into fuel.